Rent taxation in a small open economy: the effect on transitional generations - Marko Koethenbuerger; Panu Poutvaara (Institute for the Study of Labor (IZA), 2007)
We show that taxation of rents may yield an intergenerational Pareto-improvement in a small open economy provided tax revenues are earmarked to reduce wage taxes. Previous literature has shown that rent taxation benefits current young and future generations, while we show that it also benefits the current old generation when the initially prevailing tax mix is sufficiently skewed towards wage taxation.
urn:nbn:de:101:1-20080425370
Keywords: 330; Gesetzliche Rentenversicherung; Einkommensteuer; Arbeitsangebot; Generationenbeziehungen; Intertemporale Allokation; Theorie